Associative effects between fresh perennial ryegrass and white clover on dynamics of intake and digestion in sheep. (17th November 2016) - Niderkorn, V.; Martin, C.; Le Morvan, A.; Rochette, Y.; Awad, M.; Baumont, R.
Abstract: The aim of this study was to determine the associative effects between fresh perennial ryegrass and fresh white clover on intake and digestion in sheep. Five proportions of ryegrass and white clover, ranging from 0 to 1 in 0·25 increments (DM basis), were allocated to two groups of five sheep according to a replicated 5 × 5 Latin square design, and intake behaviour and digestive parameters including methane (CH4 ) emissions were measured. Feeding behaviour was affected through increased forage intake when the proportion of white clover was increased, and there were positive associative effects on intake, eating time and eating rate during the main meals consumed immediately after feed was given. These effects seemed to be related to a greater motivation to eat, rather to more efficient digestion, as no difference on DM digestibility (average 766 g kg −1 ) was detected. There were no differences in CH4 yield (average 18·1 g kg −1 DM intake) among the treatments. The optimal proportion of white clover fed with ryegrass to optimize intake and digestion was between 0·25 and 0·50. These results indicate that mixing perennial ryegrass and white clover positively affects forage intake in sheep and their motivation to eat.